Accelerated bioethanol fermentation by using a novel yeast immobilization technique: Microtube array membrane. Issue 10 (October 2015) - Chen, Chien-Chung; Wu, Chien-Hui; Wu, Jhih-Jhong; Chiu, Chien-Chih; Wong, Chien-Hsuan; Tsai, Min-Lang; Lin, Hong-Ting Victor
Graphical abstract